Construction of the aequorea Victoria green fluorescent protein (gfp) for expression in mycobacterium sp - Najamudin, Khairal Ezani (2003)
The development of sensitive methods for observing individual bacterial cells in a population in experiment and natural environments is very crucial for rapid development of anti-mycobacterial drugs. This is because more pathogenic Mycobacteria are slow growing organisms, and therefore the screening compounds for anti-mycobacterial activity is slow and inefficient. Previously, studies have been done using fluorescent bacteria that expressing 13- galactosidase (21 ), and luciferase (3) as a high screening format for antimicrobial activity. However, one drawback of these systems is that substrates such as luciferin have to be added at the required time points to induce fluorescence. Recently Green Fluorescent Protein (GFP) has become a valuable and favourite tool as a marker of growth, which could be used for screening of antimicrobial activity. This is because the marker can be visualised without interruption or termination of an experiment as is required with the detection of other commonly used markers such as B-galactosidase and luciferase. In this study a synthetic gene of GFP was constructed with mycobacteria codon bias using assembly PCR. A strong mycobacterial promoter from 65 kD mycobacterial heat shock protein was added to derive the expression. The constructed gene was cloned into vector and transformed into Escherichia coli. The ultimate aim is to use the recombinant plasmid carrying the synthetic gene with mycobacterial codon bias to create a recombinant fluorescing BCG, whichcan be used as a tool for screening compound libraries for anti-mycobacterial activity.